Transliteration of Braille Character to Gujarati Text – The Application - Vyas, HA; Virparia, P.V (International Journal of Computer Sciences and Engineering, 2019)
Technology has a significant contribution in the digital communication for visually impaired persons. There is a significant need transliteration of Braille Characters into regional language. The “Software for Transliteration of Braille Character to Gujarati Text using Python” has three key factors keep in mind. First there is digital communication using technology to provide alternative means of reading and writing. Next, technology can help in the production of digital content converted from Braille to Gujarati or vice versa. A third factor for technology is to provide improved access to information like import, export and saving the digital content. It is sometimes quite difficult to be certain whether a technology or system will meet particular needs or not. This paper is about developing a prototype using Python Programming Language, because Python is a suitable language for both learning and real world programming. Python is an extremely potent and high level objectoriented programming language. We have provided various techniques describe as a literature to develop the tool and also identified the challenges that might be faced at the time of recognition and conversion.